Contribution of Technology Adoption to the Environmental and Socio-Economic Conditions of Vegetable Producers in Svay Rieng Province - Hong Chhun; Chun Nimul; Buntong Borarin; Serey Mardy; Sao Vibol; Chan Bunyeth; Tum Saravuth; Ros Vanchey (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Extension workers have been instrumental in encouraging farmers to adopt new technologies, aiming to improve productivity, income, social status, and climate resilience. This study investigates challenges in technology adoption and its impact on vegetable production, economic and social enhancement, and climate resilience in Svay Rieng province. Data from 302 agricultural cooperative members were analyzed using Pearson’s correlation to examine relationships and linear regression to predict factors influencing farmers' achievements. Results show that internal challenges (labor, capital, technical know-how) significantly influence success, followed by external challenges. Investments in hard technologies (e.g., net houses, drip irrigation) strongly correlated with achievements, while soft technologies (technical knowledge) had a lesser impact. Regression analysis identified internal challenges and adoption of hard technologies as key predictors, explaining 25% of overall performance, including 36%, 29%, and 25% of economic, social, and climate resilience improvements, respectively. For production, only internal challenges and hard technologies were determinants, predicting 30%. Addressing internal challenges and enhancing technology applications are critical to improving vegetable producers' success in the province.